Nonverbal behavior markers in artistic texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with non-verbal behavior markers in artistic texts. It is emphasized that lexeme on the notation of nonverbal behavior of characters in artistic texts are the means of depicting their psychological condition and the stylization of direct live communication. It was shown that non-verbal markers are the system of non-speaking signs that are used as means of exchange of information between people. Body movement, gestures, face expressions and walking are considered as elements of non-verbal behavior. These means supplement the content of a verbal message about the heroes. It was emphasized that the expression of the eyes is an important part in creating a psychological portrait of a literary hero, an expression of his attitude towards others. It is the eyes that can express readiness for communication, control over the partner and his behavior. Such kinetic means as face expression is skillfully used by writers to realistic representation  of literary heroes and reproduction  of their emotions and feelings. Lexeme on the notation of body movements and gestures present ethnocultural behavioral systems. Markers of non-verbal etiquette behavior of Ukrainians are noted as an important pictorial tool.
Keywords: nonverbal behavior; communication; kinetic nonverbal means; eye contact; walking; gestures